2015
DOI: 10.1021/acs.inorgchem.5b01921
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion-Corrected Relativistic Density Functional Theory (DFT) Calculations of Structure and 119Sn Mössbauer Parameters for M≡SnR Bonding in Filippou’s Stannylidyne Complexes of Molybdenum and Tungsten

Abstract: (119)Sn Mössbauer isomer shift (IS) and quadrupole splitting (ΔEQ) for M≡SnR bonding in metal-stannylidyne complexes trans-[Cl(PMe3)4Mo≡Sn-R] (1), trans-[Cl(PMe3)4W≡Sn-R] (2), trans-[Cl(dppe)2Mo≡Sn-R] (3), trans-[Cl(dppe)2W≡Sn-R] (4), [(dppe)2Mo≡Sn-R](+) (5), [(dppe)2W≡Sn-R](+) (6) (R = C6H3-2,6-Mes2) have been investigated for the first time. Calculations of optimized structures and (119)Sn Mössbauer parameters were carried out at the DFT/TPSS-D3(BJ)/TZVPP/ZORA level of theory. The calculated geometry paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…We envisaged to develop a new synthetic approach to silylidyne complexes using silyliumylidenes based on the following conception. Quantum chemical bonding analyses of the presently known heavier tetrylidyne complexes [L n ME–R] (E = Si–Pb, R = organyl group) revealed that the M–E bonds between the negatively charged metal M and the positively charged tetrel atom E are quite polar and composed of a σ bond, polarized toward the tetrel atom E, and two π bonds, which are polarized toward the metal center M . The ME–R bonding can thus be reasonably well described in terms of the Dewar–Chatt–Duncanson model to comprise a σ-donation from the tetryliumylidene [ER] + ligand to the anionic transition-metal fragment [L n M] − and two [L n M] − → [ER] + π-backdonations, similar to the MC bonding in Fischer-type carbyne complexes .…”
Section: Introductionmentioning
confidence: 99%
“…We envisaged to develop a new synthetic approach to silylidyne complexes using silyliumylidenes based on the following conception. Quantum chemical bonding analyses of the presently known heavier tetrylidyne complexes [L n ME–R] (E = Si–Pb, R = organyl group) revealed that the M–E bonds between the negatively charged metal M and the positively charged tetrel atom E are quite polar and composed of a σ bond, polarized toward the tetrel atom E, and two π bonds, which are polarized toward the metal center M . The ME–R bonding can thus be reasonably well described in terms of the Dewar–Chatt–Duncanson model to comprise a σ-donation from the tetryliumylidene [ER] + ligand to the anionic transition-metal fragment [L n M] − and two [L n M] − → [ER] + π-backdonations, similar to the MC bonding in Fischer-type carbyne complexes .…”
Section: Introductionmentioning
confidence: 99%